Referral and triage of patients with transient ischemic attacks to an acute access clinic: risk stratification in an Australian setting. (12th March 2013) - Magin, Parker; Lasserson, Daniel; Parsons, Mark; Spratt, Neil; Evans, Malcolm; Russell, Michelle; Royan, Angela; Goode, Susan; McElduff, Patrick; Levi, Christopher
Abstract : Background: Transient ischemic attacks and minor stroke entail considerable risk of completed stroke but this risk is reduced by prompt assessment and treatment. Risk can be stratified according to the ABCD2 prediction score. Current guidelines suggest specialist assessment and treatment within 24 h for high‐risk event (ABCD2 score 4–7) and seven‐days for low‐risk event (ABCD2 score ≤ 3). Aims: The study aims to establish paths to care and outcomes for patients referred by general practitioners and emergency departments to an Australian acute access transient ischemic attack service. Methods: This is a prospective audit. Primary outcomes were time from event to referral, from referral to clinic appointment, and from event to appointment. ABCD2 score was calculated for each event. Time from event was modeled using Cox proportional hazards regression. Results: There were 231 clinic attendees (general practitioner: 127; emergency department: 104). Mean time from event to referral was 9·2 days (SD 23·7, median 2), from referral to being seen in the clinic was 13·6 days (SD 19·0, median 7), and from event to being seen in the clinic was 17·2 days (SD 27·1, median 10). Of low‐risk patients, 38·5% were seen within seven‐days of event. Of high‐risk patients, 36·7% were seen within one‐day. ABCD2 score was not a significant predictor of any time interval from event to clinic attendance. There were no completed strokes prior to clinic attendance. Conclusions: Times from event to clinic assessment were in excess of current recommendations and risk stratification was suboptimal, though short‐term outcomes were good. Improvements in referral mechanisms may enhance risk‐stratification and triage.